Analysis of the COVID-19 Severity Based on NLR and the Mortality Rate of Pregnant Women with COVID-19 at Dr. Moewardi General Hospital, Surakarta, Central Java, Indonesia - Dhea Fitria Rachma; Teguh Prakosa; Sigit Setyawan; Abdurahman Laqif (Indonesian Journal of Medicine, 2022)
Background: Coronavirus Disease 2019 (COVID-19) is a disease of the human respiratory system. Pregnant women are more susceptible to respiratory infections due to physiological changes in the immune and cardiopulmonary systems. Routine laboratory biomarkers such as lymphocytes, neutrophils, and NLR are considered prognostic in COVID-19. This study aimed to analyzed the severity of COVID-19 based on NLR on the mortality of pregnant women with COVID-19 at Dr. Moewardi, Surakarta.Subjects and Method: This study used analytic observational with a cross-sectional. The study subjects were 82 pregnant women with confirmed COVID-19, aged over 18 years, and being treated at RSUD Dr. Moewardi Surakarta between March 2020 to January 2022. The samples were taken using the consecutive sampling technique. The independent variable is the severity of COVID-19 based on clinical presentation. The dependent variable is the laboratory results in lymphocytes, neutrophils, and NLR. Data were collected from medical records and anlayzed using SPSS software.Results: There was correlation between NLR on the severity of pregnant women with COVID-19 (Mean= 10.11; SD= 4.10; p= 0.026) and there was a significant correlation between NLR on the mortality rate of pregnant women with COVID-19 (Mean= 9.92; SD= 3.94; p<0.001).Conclusion: NLR affected the severity and the mortality rate among pregnant women with COVID-19.Keywords: COVID-19, pregnancy, lymphocytes, neutrophils, NLR, mortalityCorrespondence: Dhea Fitria Rachma. Faculty of Medicine Universitas Sebelas Maret Surakarta. Jl. Ir. Sutami 36A, Surakarta 57126, Indonesia. Email: dheaf1020@student.uns.ac.id. Mobile: 085702594898.Indonesian Journal of Medicine (2022), 07(04): 401-410https://doi.org/10.26911/theijmed.2022.07.04.05